A dual conditional CRISPR-Cas9 system to activate gene editing and reduce off-target effects in human stem cells - Seung Bum Park; Takuro Uchida; Samantha Tilson; Zongyi Hu; Christopher D. Ma; Madeleine Leek; Michael Eichner; So Gun Hong; T. Jake Liang (Elsevier, 2022)
The CRISPR-Cas9 system has emerged as a powerful and efficient tool for genome editing. An important drawback of the CRISPR-Cas9 system is the constitutive endonuclease activity when Cas9 endonuclease and its sgRNA are co-expressed. This constitutive activity results in undesirable off-target effects that hinder studies using the system, such as probing gene functions or its therapeutic use in humans. Here, we describe a convenient method that allows temporal and tight control of CRISPR-Cas9 activity by combining transcriptional regulation of Cas9 expression and protein stability control of Cas9 in human stem cells. To achieve this dual control, we combined the doxycycline-inducible system for transcriptional regulation and FKBP12-derived destabilizing domain fused to Cas9 for protein stability regulation. We showed that approximately 5%-10% of Cas9 expression was observed when only one of the two controls was applied. By combining two systems, we markedly lowered the baseline Cas9 expression and limited the exposure time of Cas9 endonuclease in the cell, resulting in little or no undesirable on- or off-target effects. We anticipate that this dual conditional CRISPR-Cas9 system can serve as a valuable tool for systematic characterization and identification of genes for various pathological processes.